Download presentation

Presentation is loading. Please wait.

Published byRebecca Young Modified over 7 years ago

1
Solve an equation by combining like terms EXAMPLE 1 8x – 3x – 10 = 20 Write original equation. 5x – 10 = 20 Combine like terms. 5x – 10 + 10 = 20 + 10 Add 10 to each side. 5x = 30 Simplify. Divide each side by 5. x = 6 Simplify. = 30 5 5x5x 5 Solve

2
EXAMPLE 2 Solve an equation using the distributive property 7x + 2(x + 6) = 39. SOLUTION When solving an equation, you may feel comfortable doing some steps mentally. Method 2 shows a solution where some steps are done mentally. Solve

3
EXAMPLE 2 METHOD 1 Show All Steps 7x + 2(x + 6) = 39 7x + 2x + 12 = 39 9x + 12 = 39 9x + 12 – 12 = 39 – 12 9x = 27 x = 3 = 9x9x 9 27 9 METHOD 2 Do Some Steps Mentally 7x + 2(x + 6) = 39 7x + 2x + 12 = 39 9x + 12 = 39 9x = 27 x = 3

4
Standardized Test Practice EXAMPLE 3 SOLUTION ANSWER The correct answer is D. A CD B In Step 2, the distributive property is used to simplify the left side of the equation. Because – 4( x – 3) = – 4 x+ 12, Step 2 should be 5x – 4x + 12 = 17.

5
Write original equation. 7d + 4 = 32 Combine like terms. 7d + 4 – 4 = 32 – 4 Subtract 4 from each side. 7d = 28 Simplify Divide each side by 5. d = 4 Simplify. = 28 7 7d7d 7 GUIDED PRACTICE for Examples 1, 2, and 3 9d – 2d + 4 = 32 1. 9d – 2d + 4 = 32 Solve the equation. Check your solution.

6
Check GUIDED PRACTICE for Examples 1, 2, and 3 9d – 2d + 4 = 32 Write original equation. Substitute 4 for d. Multiply. 32 = 32 Simplify. Solution checks. 9(4) – 2(4) + 4 = 32 ? 36 – 8 + 4 = 32 ?

7
EXAMPLE 2 2w + 3w + 12 = 27 5w + 12 = 27 5w + 12 – 12 = 27 – 12 5w = 15 w = 3 = 5w5w 5 15 5 GUIDED PRACTICE for Examples 1, 2, and 3 2w + 3(w + 4) = 27 2. 2w + 3(w + 4) = 27 Solve the equation. Check your solution.

8
Check GUIDED PRACTICE for Examples 1, 2, and 3 Write original equation. Substitute 3 for w. Multiply. Simplify solution checks. 2w + 3(w +4) = 27 27 = 27 Simplify. 2(3) + 3(3 + 4) = 27 ? 6 + 21 = 27 ? 6 + 3(7) = 27 ?

9
EXAMPLE 2 6x – 2x + 10 = 46 4x + 10 = 46 4x + 10 – 10 = 46 – 10 4x = 36 x = 9 = 4x4x 4 36 4 GUIDED PRACTICE for Examples 1, 2, and 3 6x – 2(x – 5) = 46 3. Solve the equation. Check your solution. 6x – 2(x – 5) = 46

10
Check GUIDED PRACTICE for Examples1, 2, and 3 6x – 2(x – 5) = 46 46 = 46 6(9) – 2(9 – 5) = 46 ? 54 – 8 = 46 ? 54 – 2(4) = 46 ?

Similar presentations

© 2023 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google